2007
DOI: 10.1002/adma.200601957
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Characterization of Metal Electrode Performance for Electric‐Field‐Induced Resistance Switching in Metal/Pr0.7Ca0.3MnO3/Metal Structures

Abstract: Electric-field-induced switching of resistance [1][2][3][4][5][6][7] has attracted great interest for potential applications in high-performance nonvolatile memory devices known as resistance random access memory (RRAM). [8] Compared to other nonvolatile memory, RRAM has several advantages, such as fast writing times, high densities, and low operating voltages. Switching behavior, as characterized by current-voltage (I-V) data, has been reported in various materials, including metal oxides [1][2][3][4][5][6] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 13 publications
1
60
1
Order By: Relevance
“…Thanks to recent further intensive investigations, there exists some general agreements in oxides that the migration of oxygen vacancies (or oxygen ions) under an applied electric field plays an important role [5,7,[13][14][15] and that interface effects are more pronounced than bulk switching. [10][11][12]15] Two basic models have been proposed: (i) local redox process based on oxygenvacancy migration (or oxygen diffusion) [9] including an electrochemical interface reaction [5] and (ii) change in Schottky-like barrier height and/or width by trapping/detrapping effects at interface defect states. [11] Although no attention has been paid to it in the literature yet, these two mechanisms exhibit different switching polarities.…”
mentioning
confidence: 99%
“…Thanks to recent further intensive investigations, there exists some general agreements in oxides that the migration of oxygen vacancies (or oxygen ions) under an applied electric field plays an important role [5,7,[13][14][15] and that interface effects are more pronounced than bulk switching. [10][11][12]15] Two basic models have been proposed: (i) local redox process based on oxygenvacancy migration (or oxygen diffusion) [9] including an electrochemical interface reaction [5] and (ii) change in Schottky-like barrier height and/or width by trapping/detrapping effects at interface defect states. [11] Although no attention has been paid to it in the literature yet, these two mechanisms exhibit different switching polarities.…”
mentioning
confidence: 99%
“…As can be seen, V Set and V Reset distribute in a range of 0.3 V to 1 V and -0.3 V to -0.9 V, respectively. The switching threshold voltages of the Cu/GO/Pt sandwiched structure are lower than those of most reported RRAM devices (Szot et al, 2006;Tsubouchi et al, 2007;Guan et al, 2007;Fujiwara et al, 2008;Li et al, 2008). The retention performance of the Cu/GO/Pt memory cell at room temperature is shown in Fig.…”
Section: Morphology Of Go Sheets and Thin Filmsmentioning
confidence: 90%
“…There are questions as to whether resistance switching happens inside the insulator layers [2,3] or at the interfaces between metal electrodes and insulator layers [4][5][6][7][8][9]. In the case of epitaxial Pr 1−x Ca x MnO 3 , the resistance switching occurs at the interfaces between Pr 1−x Ca x MnO 3 and metal electrodes which can form Schottky-like barrier with Pr 1−x Ca x MnO 3 [6,10]. Our previous research also has revealed that the resistance switching occurs at the Al/Pr 1−x Ca x MnO 3 interfaces [10].…”
Section: Introductionmentioning
confidence: 98%
“…In the case of epitaxial Pr 1−x Ca x MnO 3 , the resistance switching occurs at the interfaces between Pr 1−x Ca x MnO 3 and metal electrodes which can form Schottky-like barrier with Pr 1−x Ca x MnO 3 [6,10]. Our previous research also has revealed that the resistance switching occurs at the Al/Pr 1−x Ca x MnO 3 interfaces [10]. For more deeply understanding the resistance switching at the Al/Pr 1−x Ca x MnO 3 interfaces, investigations of device size dependences of resistance switching performances are needed.…”
Section: Introductionmentioning
confidence: 99%